2017
DOI: 10.1128/jb.00107-17
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Function, and Detection of Protein Acetylation in Bacteria

Abstract: N -Lysine acetylation is now recognized as an abundant posttranslational modification (PTM) that influences many essential biological pathways. Advancements in mass spectrometry-based proteomics have led to the discovery that bacteria contain hundreds of acetylated proteins, contrary to the prior notion of acetylation events being rare in bacteria. Although the mechanisms that regulate protein acetylation are still not fully defined, it is understood that this modification is finely tuned via both enzymatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(141 citation statements)
references
References 147 publications
(171 reference statements)
3
135
0
1
Order By: Relevance
“…SIRT3, a deacetylase, was shown to deacetylate and increase CS activity [8]. Although firstly discovered and extensively studied in eukaryotic histones and transcription-associated factors, lysine acetylation is also known to play important roles in bacterial physiology [9][10][11][12]. Acetylome studies have identified multiple lysine acetylation sites in the E. coli Type II CS [13], but their functions are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT3, a deacetylase, was shown to deacetylate and increase CS activity [8]. Although firstly discovered and extensively studied in eukaryotic histones and transcription-associated factors, lysine acetylation is also known to play important roles in bacterial physiology [9][10][11][12]. Acetylome studies have identified multiple lysine acetylation sites in the E. coli Type II CS [13], but their functions are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…62,63 Protein acetylation increases the net negative charge 62,64 on DNA binding proteins that might inhibit their binding capacity of the positively charged lysine residues with the negatively charged phosphate groups on DNA as reviewed by Carabetta et al 5 The inhibitory effect of acetylation on K residues found in the active sites of enzymes ACS, NhoA, adenosylmethionine synthase (MAT), and MbtA is highlighted in this review.…”
Section: Resultsmentioning
confidence: 94%
“…25 Increasing evidence supports the presence and role of lysine acetylation in mycobacteria. 612 In Mtb, lysine acetylation presumably confers protein stability and compartmentalization, thereby modulating diverse cellular processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Активація сиртуїнів обмеженням калорій або за допомогою фармакологічних засобів продовжує тривалість життя і сприяє збереженню нормального перебігу процесів організмів − від дріжджів до ссавців. Це ще раз підкреслює доцільність розробки лікар-ських засобів, мішенню яких є сиртуїни, для терапії хвороб, опосередкованих старінням [9,10].…”
Section: вступunclassified